2020
DOI: 10.1093/cid/ciaa005
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria in Metro Manila, the Philippines 2006–2017: A Clinical, Molecular, and Spatial Characterization

Abstract: Background Diphtheria is a vaccine-preventable disease that persists as a global health problem. An understanding of the pattern of disease is lacking in low- and middle-income countries such as the Philippines. Methods We conducted a retrospective review of the clinical, microbiological, and epidemiological features of patients admitted with a clinical diagnosis of diphtheria to an infectious disease referral hospital in Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The most common STs (ST67) and the ST209 have also been identified in diphtheria outbreaks in the western and central highlands of Vietnam recently, implying the sustained circulation of these STs across the country [ 28 ]. ST67 was the most common genotype associated with diphtheria in an observational studies from San Lazaro Hospital in the Philippines and in Europe [ 49, 50 ], whereas ST258 and ST209 were both reported in Thailand in 2012 [ 51 ]. Estimating within-group SNP variation for different STs in our study showed SNP numbers varied substantially within these STs; the average of SNP difference in ST67 was 65 (range: 51-83 SNPs), 39 in ST151 (range: 32-49 SNPs), 32 in ST258 (range: 29-36 SNPs) and 20 in ST455 (range: 17-26 SNPs).…”
Section: Discussionmentioning
confidence: 99%
“…The most common STs (ST67) and the ST209 have also been identified in diphtheria outbreaks in the western and central highlands of Vietnam recently, implying the sustained circulation of these STs across the country [ 28 ]. ST67 was the most common genotype associated with diphtheria in an observational studies from San Lazaro Hospital in the Philippines and in Europe [ 49, 50 ], whereas ST258 and ST209 were both reported in Thailand in 2012 [ 51 ]. Estimating within-group SNP variation for different STs in our study showed SNP numbers varied substantially within these STs; the average of SNP difference in ST67 was 65 (range: 51-83 SNPs), 39 in ST151 (range: 32-49 SNPs), 32 in ST258 (range: 29-36 SNPs) and 20 in ST455 (range: 17-26 SNPs).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory diphtheria can present as a critical illness among children in the Philippines and physicians order blood culture to rule out other severe bacterial infections [ 37 ]. All blood cultures were negative in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases such as Acute Flaccid Paralysis (AFP) [6], Diphtheria [7], and Measles [8] have long been signi cant concerns. These diseases, which once saw widespread prevalence, have been substantially controlled through concerted public health efforts.…”
Section: Introductionmentioning
confidence: 99%